Projetos como metodologia de ensino de língua inglesa para surdos - Oliveira, Alexandra Ohana Andreatta de (Universidade do Vale do Rio dos Sinos, 2018)
In the current scenario Brazilian deaf people live it is expected that, besides learning their first language, they must learn Portuguese, and according to the Brazilian National Curricular Parameters (PCNs), they ought to learn a foreign language as well. The Deaf Education is a research area of constant development, but there is insufficient research concerning methodologies of English teaching for this specific audience. The aim of this study is to reflect and discuss about how project work, proposed by Stoller (2002), contributes to deaf students’ English learning, considering it a new viable methodology for teaching English in a non-governmental and non-profit organization that promotes a bilingual education for the deaf. This is a qualitative research study, it was developed in a private school, in Rio Grande do Sul, affiliated to a non-governmental and non-profit organization, called Associaçao de Pais e Amigos dos Deficientes Auditivos (APADA), and its main objective is to ensure the access of deaf people to basic education in the Vale do Rio dos Sinos region. The data was gathered through the practice of project work registered in video and photographs. The results are considered optimistic. It is possible to notice that not all the positive outcomes proposed by Stoller (2006) are completely present in the six activities explored, some are identified only partially present in the data. The authenticity of experience and the language contact by the students were identified in all the analyzed activities. However, the learners’ motivation and involvement were completely and partially present in the activities and can be related to several variables proposed by Stoller (2006). An improved relationship between the students in group work was the benefit that stood out in the activities and it is related to the knowledge exchange between the learners in the classroom. Aspects such as self-confidence, autonomy and initiative by the students were some of the benefits least present in this research study. Although, through the reported reflections and outcomes, it is possible to think about project work as an applicable and favorable methodology for teaching English to the deaf.
Keywords: Educação de surdos; Projetos; Língua inglesa; Metodologia de ensino; Deaf education; Projects; Teaching methodology; English